Establishment of the Norwegian hearing register for children - Mattsson, Tone Stokkereit; Nilsen, Ann Helen; Wennberg, Siri (Frontiers in Human Neuroscience, 2024)
The Norwegian Directorate of Health approved the Norwegian Hearing Register for Children in 2022. The main objective of the register is to improve the quality of treatment for children with permanent hearing loss, by measures, follow-ups and monitoring the quality and results of the health care system.Inclusion criteria are children who do not pass universal newborn hearing screening and/or children with permanent hearing loss < 18 years of age. Hearing loss is defined as pure-tone audiometry threshold of (PTA4) > 20 dB in at least one ear.Data are registered at the Ear, Nose and Throat departments at inclusion and at follow-ups at the age of 3, 6, 10 and 15 years. The register collects information about the child within a holistic perspective. The key elements of the register are a) data concerning newborn hearing screening; b) data concerning hearing, medical information, hearing amplification and intervention c) patient reported outcome measures registered by caregivers using three questionnaires; Pediatric Quality of Life Inventory, Strengths and Difficulties Questionnaire and Parents' Evaluation of Aural/Oral Performance of Children.The register has established four quality indicators regarding newborn hearing screening and early intervention a) the rate of true positive neonatal screens; b) testing for congenital cytomegalovirus within 3 weeks of age for children who do not pass newborn hearing screening; c) audiological testing within 4 weeks of age for children who do not pass newborn hearing screening ; c) audiological evaluation to confirm the hearing status no later than 3 months of age and d) early intervention before 6 months of age.The register will include the total population of hearing impaired children over long time periods. Thus, the register enables each hospital to monitor their quality indicator scores continuously and compare them with national levels in real time. This facilitates and accelerate identification of improvement areas in the hospitals and will be an important contributor for quality improvement in NHS, diagnostics and hearing intervention for children in Norway. In addition, data from the register will be a unique source for research, and study designs with a long follow-up time can be applied.